Jezikovni model umetne inteligence chatGPT kot pripomoček pri kvalitativni analizi - Mesec, Blaž (Socialno delo, 2023)
The text describes an experiment that used the language model of artificial intelligence called ChatGPT for the qualitative analysis of a response from a social work student to an interview question about her study practice. ChatGPT was asked questions about identifying basic themes, concepts, typologies, and evaluations. The robot provided surprisingly appropriate answers, but it rejected self-critically the request for professional conceptualization. The conclusion of the informal experiment is that ChatGPT is a useful tool in qualitative analysis, provided that the researcher can ask appropriate questions (prompts). However, the output of the robot must be evaluated and supplemented by a human researcher before final report and publication. The issue of authorship and responsibility is raised.
Keywords: človeška inteligenca; grounded theory; heuristics; hevristika; human intelligence; kvalitativna analiza; mentorship; mentorstvo; methodology; metodologija; study practicum; študijska praksa; utemeljena teorija